The Effectiveness Of Natoni In Timor Dawan Customs : English - Yanti Boimau Yanti; Kadek Ayu Cintya Adelia Kadek (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2019)
The number of tribes that inhabit the Indonesian nation differs in ethnicity, religion, race and even language so that people who live in these differences have different cultures. Culture is a way of life that develops and is shared by a group of people and is passed down from generation to generation. Culture that is maintained and carried out continuously or repeatedly can be called a tradition. One of the cultures in the Timorese society that has become a tradition and is still being preserved today is